2020
DOI: 10.1002/cphc.201901071
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient, Robust New Scheme for Establishing Broadband Homonuclear Correlations in Biomolecular Solid State NMR

Abstract: An efficient mixing scheme is introduced for establishing two‐dimensional (2D) homonuclear correlations based on dipolar couplings. This mixing scheme achieves broadband dipolar recoupling using remarkably low powers even under ultrafast magic‐angle spinning (MAS) rates. This Adiabatic Linearly FREquency Swept reCOupling (AL FRESCO) method applies a series of weak frequency‐chirped pluses on the 1H channel, for performing efficient 13C−13C magnetization transfers leading to cross peaks between sites separated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…6 For example, the newly developed adiabatic frequency-swept recoupling scheme AL FRESCO might be an excellent candidate for implementation at moderate and fast spinning speeds. 56 Moreover, we have demonstrated that 1D DARR difference can be used to quickly obtain detailed performance metrics of various recoupling methods and the effect of spinning speed, which should prove valuable to researchers developing new schemes or choosing between existing ones.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 For example, the newly developed adiabatic frequency-swept recoupling scheme AL FRESCO might be an excellent candidate for implementation at moderate and fast spinning speeds. 56 Moreover, we have demonstrated that 1D DARR difference can be used to quickly obtain detailed performance metrics of various recoupling methods and the effect of spinning speed, which should prove valuable to researchers developing new schemes or choosing between existing ones.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Alternatively, if no RF power is applied during the mixing period, the experiment becomes the selective 1D equivalent to the 2D PDSD method. If higher MAS spinning speeds are used, the DARR recoupling scheme could be easily replaced by recoupling programs better suited for higher MAS frequencies (CORD, AL FRESCO, and PARIS). ,, A 13 C hard pulse is then used to read out chemical shift-selected spin-diffusion edited 13 C magnetization. Importantly, the receiver phase is alternated every other scan by 180°, matched with on- and off-power selective pulses.…”
Section: Resultsmentioning
confidence: 99%
“…However, both PDSD and DARR sequences are most efficient for correlating spin pairs with small ΔΩ ij and around R 2 conditions. , The effective recoupling bandwidth would be insufficient at faster MAS rates (>22 kHz) for correlating the surrounding homonuclear spins with a wide range of chemical shifts, as required in NCACX and NCOCX types of experiments. In this sense, many kinds of broadband SD-based sequences with (phase-, amplitude-, and/or resonance frequency)-modulated RF irradiation (Figure ), such as PARISxy, SHA+, CORDxy, AM-MIRROR (Amplitude-Modulated MIRROR), and AL FRESCO (Adiabatic Linearly FREquency Swept reCOupling), have been developed for improving the effective recoupling bandwidth at faster MAS rates. Nowadays, some of these broadband SD-based sequences have already been used in NCACX and NCOCX type experiments of practical biological systems for homonuclear correlations at moderate and fast MAS rates (see Table ).…”
Section: Homonuclear Dipolar Recoupling Techniques and Applicationsmentioning
confidence: 99%
“…Copyright 2013 Elsevier. Parts of (D) (variants of AL-FRESCO) have been reproduced with permission from ref . Copyright 2019 Wiley, respectively.…”
Section: Polarization Transfermentioning
confidence: 99%